Visuospatial pathways to mathematical achievement. (August 2019) - Chan, Winnie Wai Lan; Wong, Terry Tin-Yau
Abstract: Children having better visuospatial working memory, or the capacity to store and manipulate visuospatial information, perform better in mathematics. Yet, the underlying mechanisms are not well understood. In this study, we proposed a pathway model which linked up visuospatial working memory and mathematical achievement through two routes: numerical magnitude representation and problem representation. The data were drawn from 541 children who were assessed in both Grades 1 and 2. Using path analysis, we found that the association between visuospatial working memory and mathematical achievement was mediated by the deployment of visuospatial processes for magnitude representation (magnitude representation pathway) as well as for problem representation in solving mathematical problems (problem representation pathway). Such findings offer an important framework for developing intervention strategies to help children with poor visuospatial working memory in learning mathematics. Highlights: Visuospatial working memory is significantly related to math achievement. The relation is mediated by the representations of both magnitude and problem schema. The findings increase our understanding of the spatial-math association.